PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH ATONIK PADA DUA VARIETAS TANAMAN JAHE (Zingiber officinale) PADA PERTUMBUHAN FASE VEGETATIF - Ardito Risano; Sutini Sutini; Didik Utomo Pribadi (Plumula : Berkala Ilmiah Agroteknologi, 2023)
The ginger plant (Zingiber officinale) is one of the plant commodities included in the Zingiberaceae family known as ginger. The ginger plant was the most popular spice and was used by Europeans in antiquity. Apart from being an herbal plant, the ginger plant stores antioxidant substances that are useful for the health of the human body. In 2016, ginger crop production tended to decline while demand continued to increase. Therefore, the breeding of ginger plants can be carried out using growth regulators auxin which can spur the growth and development ginger. The purpose of this study was to determine the optimal formulation against the growth of ginger in the vegetative phase. The study was conducted from February to April in Agricultural Land, Faculty of Agriculture, University of National Development "Veteran" East Java. This study used an experiment compiled using a Complete Randomized Design (RAL) and repeated 3 times. Factor I Atonic ZPT Concentration of 0 ml/l (control), Atonic ZPT Concentration of 2 ml/l, Atonic ZPT Concentration of 4 ml/l, Atonic ZPT Concentration of 6 ml/l, Atonic ZPT Concentration of 8 ml/l, and Atonic ZPT Concentration of 10 ml/l. Factor II Emprit Ginger Variety, and Red Ginger Variety. The results showed that the difference in the dose of atonic growth regulator (ZPT) concentration against dry weight in the vegetative phase had a BNT value of 5% amounting to 7.95. This is because proper administration of auxin can increase nutrient absorption through the roots. In the results of the study, there was also a noticeable difference in the differences in ginger plant varieties that differed markedly from the root length with a BNT value of 5% amounting to 12.46. This is because the hormone can spur and spur biochemical activity. In the diameter of the stem, there is a noticeable difference in the difference in ginger plant varieties which is significantly different with a LSD value of 5% amounting to 0.36. This is because the material used to support the formation of rhizomes is available in large supply, the rhizomes formed are larger and affect the diameter of the rhizomes.